Flow Electrochemical Cyclizations via Amidyl Radicals: Easy Access to Cyclic Ureas - Ahmed, Nisar; Vgenopoulou, Aggeliki (SynOpen, 2019)
Flow chemistry has advantages over batch processes and can achieve the synthesis of substances in high yield under safe working conditions. The combination of electrochemistry and flow microreactor technology has made chemical transformations possible without the use of oxidants or catalysts. Herein, we report flow electrosynthesis of cyclic ureas via oxyamination of N-allylic ureas. We have found that continuous flow is able to outperform its batch counterpart, producing cyclic ureas in excellent yields.
Keywords: alkenes functionalization; microreactor technology; flow electrosynthesis; oxyamination; cyclic ureas